An Analysis of the Disconnection Between Urban Schools and Science Education - Elliott, Volda; Lashley, Lidon (Social Science Learning Education Journal, 2017)
This study focused on reasons why Science in Urban School Districts has been poorly received, and identified appropriate strategies necessary to help learners become confident in gaining better understanding in Chemistry. A high percentage of our studentsâ have failed to achieve passing grades on the statewide Chemistry Examination.This research described several obstacles that contribute to studentsâ poor performances in Chemistry.Â Based on the findings from Clara Barton and Paul Robeson High Schools, adequate professional development and collaboration of human resources are key ingredients for dissolving the misconception of Chemistry awareness among our students.Â The action plan focused on: (1) improving studentsâ achievement on the Statewide Chemistry Regents Examination (2) providing teachersâ opportunities to implement monitor and evaluate new teaching practices (3) developing Chemistry workshops to increase collaboration and collegiality between principals, assistant principals, coaches, teachers and specialist from the district office. This plan was primarily aimed on having Chemistry teachers, reexamine their teaching styles and determine appropriate methods that will support students understanding of Chemistry better. This was accomplished via teachers sharing common prep time to conduct planning, assessment and decoding the Chemistry curriculum in order to eliminate irrelevant topics by aligning it with previous Chemistry Regents Examination also Science coaches will demonstrate best methods of teaching different Chemistry concepts.